Planar droplet sizing for studying the influence of ethanol admixture on the spray structure of gasoline sprays - Kögl, Matthias; Mishra, Yogeshwar Nath; Baderschneider, Kevin; Conrad, Chris; Lehnert, Bastian; Will, Stefan; Zigan, Lars (Experiments in Fluids, 2020)
Abstract: A novel planar droplet sizing (PDS) technique based on laser-induced fluorescence (LIF) and Mie-scattering is utilized for the characterization of the spray structure under gasoline direct-injection spark-ignition (DISI) conditions. Fuel effects on the spray structure and cyclic variations are studied for a gasoline surrogate fuel (Toliso, consisting of 65 vol.% isooctane and 35 vol.% toluene) and the gasoline-ethanol blend E20 (20 vol.% ethanol admixture). Sauter mean diameter (SMD) results are compared with those from phase-Doppler anemometry (PDA) measurements showing good agreement especially at early points in time (up to 1.2 ms after start of injection). The liquid spray propagation and SMD are very similar for both fuels indicating similar atomization behavior. Both investigated fuels show comparable cyclic variations of the spray shape. A larger width and slightly larger droplet sizes are observed for the E20 spray when stronger evaporation occurs (at 2 ms). At these later points in time, the PDS-measured droplet sizes differ from the PDA-results. Here the limitation of the PDS-technique becomes obvious as a partial evaporation of the droplets may lead to large systematic errors. A numerical simulation of single droplets is provided for clarification of issues of droplet evaporation in PDS. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-09-18